Creative industry to generate RM33bil in 2020 - Idris Jusoh - New Sabah Times English, (KK) (New Sabah Times English (KK), 2013)
KUALA LUMPUR: The country's creative industry has generated more than RM9.4 billion in economic value and the amount is expected to grow to RM33 billton by 2020, Second Education Minister Datuk Seri Idris Jusoh said yesterday.